Public Information, Education, and Communication (IEC) of Health: Active Participation of Health Practitioners in Urban Radio in a Low Resource Setting. Issue Volume 34:Issue s1(2019) (May 2019) - Bonney, Joseph; Osei-Tutu, Lawrence; Selormey, Richard; Hammond, Bernard; Bonsu, Patricia
Abstract : Introduction: Over the last two decades, Frequency Modulation (FM) radio has been established as the only form of sound broadcasting in Ghana. Radio is the most accessible of mass media. There are more than 40 operational radio stations in the Ashanti region of Ghana. Most stations are commercial, broadcasting in the local language (Asante-Twi). Many urban radio health slots discuss various diseases and their treatments mainly for the benefit of patients. Complementary and Alternative Medicine (CAM) practitioners who are able to pay for airtime dominate as 'experts' in most of these shows. Methods: We identified an IEC gap regarding policies governing healthcare delivery, healthcare financing, training, ethics and research, and environmental issues. In June 2015, orthodox medical practitioners collaborated with a private, local, English-speaking radio station to produce and host a weekly health show whose content was aimed at holistically discussing health from the viewpoint of practitioners, clients, policy makers, administrators, and financiers in a simplified language for the general public, including healthcare trainees. Discussion: The show dubbed "Staying Alive" first aired on Tuesday, July 7, 2015, at 20:00 GMT and continues to air to date, appealing to a wide range of active listeners. "Staying Alive" to the best of our knowledge remains the only show with a holistic approach to health. Over the last 23 months, we have experienced challenges in sustaining sponsorship to fund the cost of production and airtime for the show, and the cost of effectively assessing the public health impact of the show. Orthodox medical practitioners can employ mass radio as an effective tool for advocacy, information dissemination, and education of clients or health trainees in low or middle-income urban settings through effective collaboration with media stations.